A Comparative Analysis of the Philippine and Indonesian English Curricula at the Elementary Education Level - Asyifa, Firly; Rodliyah, Rojab Siti; Mababaya, Ahmad Dindang; Amalia, Lulu Laela (IJECA (International Journal of Education and Curriculum Application), 2025)
Curriculum plays an important role in education because it provides a structured framework for learning. Understanding how English curricula in different countries are constructed can be beneficial for improving educational quality.  This study, therefore, aimed to analyze and compare the Indonesian and Philippine English curricula, focusing on their construction, particularly at the elementary education level. The study employed document analysis through three stages. First, the data were coded using themes adapted from Tyler’s Rationale (objectives, design, scope and sequence, evaluation). Then, a comparative analysis was conducted to identify similarities and differences between the two curricula. Finally, the findings were interpreted by considering contextual and philosophical factors influencing each curriculum. Findings reveal significant differences: the Philippine curriculum introduces English from Kindergarten, highlighting its role as a second language that is vital for national development and global integration. It employs a structured approach emphasizing early exposure, higher-order thinking, and standardized assessments. By contrast, Indonesia introduces English in Grade 3, prioritizing foundational skills in the Indonesian language first; and emphasizing flexibility, formative assessments, and greater teacher autonomy, allowing contextualized adaptation to diverse student needs. Despite these differences, both curricula aim to foster communicative competence, critical thinking, and intercultural awareness, essential skills for 21st-century learners. The results bring to light the importance of context-sensitive curriculum development that balances international educational trends with local linguistic realities, contributing theoretically by clarifying how national contexts influence curriculum choices in ESL and EFL environments. Practically, it provides actionable insights for policymakers and curriculum designers aiming to develop adaptable, inclusive, and culturally relevant English programs in multilingual contexts.